Fakultatywna podstawa odroczenia wykonania kary w kodyfikacji karnej z 1997 roku - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The study contains a synthetic analysis of the optional basis for postponing the exe-cution of a custodial sentence. Considerations began with recalling the shape of the insti-tution under the previous codification. Then, all the amendments pursuant to Art. 151 of the Executive Penal Code made under the current law were analysed. Particular attention was paid to changes devoted to the legal privileges of pregnant women and persons taking care of children up to 3 years after birth and postponing the execution of the sentence for systemic reasons, completely independent of the convict, and related to overcrowding in Polish penitentiary units.
Keywords: odroczenie kary; przeludnienie jednostek penitencjarnych; wywiad środowiskowy; zawodowy kurator sądowy